SOLAR RADIATION AND CALCULATION - Fozilova Mohira Soyibjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Solar radiation is the primary driver of Earth’s energy systems and plays a critical role in renewable energy applications. This study examines the characteristics, influencing factors, and methods of calculating solar radiation. Using empirical models, satellite data, and software tools, solar radiation can be quantified for diverse applications such as photovoltaic (PV) system design, agriculture, and climate modeling. This article provides a detailed review of solar radiation, its calculation methods, and practical applications while highlighting the importance of accurate data for optimizing solar energy utilization.